Analysis of arctic kelp populations on the west coast of Svalbard, Norway - Niedzwiedz, Sarina; Voigt, Clara; Andersen, Sebastian; Diehl, Nora; Damsgård, Børge; Bischof, Kai (PANGAEA, 2025)
We assessed how Arctic kelp populations react to their local in situ environment in August 2022. Therefore, we sampled Saccharina latissima sporophytes from eight populations at several latitudes on the west coast of Svalbard, Norway, and correlated these results to the abiotic conditions they experienced. At each sampling station, similar sized sporophytes (n=5) were collected from 5±2 m water depth using a plant rake (Plant rake 19.000, acc. to Sigurd Olsen, KC Denmark, Silkeborg, Denmark). Subsamples were taken from each sporophyte by cutting discs, 2 cm² in diameter, from the meristem, within two hours of sampling. All samples were dried in silica gel, which was replaced regularly. Pigment analysis was analysed with a High-Performance Liquid Chromatograph (HPLC, LaChromElite® system, L-2200 autosampler (chilled), DA-detetctor L-2450; VWR-Hitachi International GmbH, Darmstadt, Germany). Antioxidant activity (AOA) was determined following the ABTS·+ (2,2'-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid, 7 mM in biDest H2O) assay. Total carbon and total nitrogen content were analysed with an elemental analyser (Euro EA 3000 Elemental Analyser, EuroVector S.P.A., Milano, Italy).
Keywords: Antioxidative activity; C:N; Pigments; SST; Tolerances; Underwater light climate